2020
DOI: 10.1212/wnl.0000000000010157
|View full text |Cite
|
Sign up to set email alerts
|

Pearls & Oy-sters: Bilateral globus pallidus lesions in a patient with COVID-19

Abstract: Neurologic complications are occurring in coronavirus disease 2019 (COVID-19), and these patients should be monitored for neurologic symptoms. c When evaluating abnormal imaging findings in patients with COVID-19, the presence and specific pattern of deep gray structure involvement can be an important clue to etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
(6 reference statements)
2
17
0
Order By: Relevance
“… Brun G et al [ 187 ] reported a 54 Y/O F with Multiple supra-tentorial punctiform and tumefactive lesions involving the white matter bilaterally. Demirci Otluoglu G et al [ 196 ] reported a 48 Y/O M with Acute encephalomyelitis and positive CSF for SARS-CoV2 Impaired consciousness, encephalopathy and encephalitis 11 Decreased level of consciousness And Encephalopathy 22 Articles [ 39 ], [ 40 ], [ 57 ], [ 58 ] [ 60 ], [ 62 ] [ 88 ], [ 96 ], [ 98 ], [ 100 ], [ 101 ], [ 133 ], [ 135 ], [ 136 ] [ 137 ], [ 138 ], [ 139 ] [ 140 ], [ 141 ] [ 178 ] [ 184 ] [ 189 ] [ 195 ] [ 197 ] 4,54 NR in all articles. Yin R et al [ 133 ] reported a 64 Y/O M with altered consciousness and Psychiatric symptoms, his brain CT scan was Normal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Brun G et al [ 187 ] reported a 54 Y/O F with Multiple supra-tentorial punctiform and tumefactive lesions involving the white matter bilaterally. Demirci Otluoglu G et al [ 196 ] reported a 48 Y/O M with Acute encephalomyelitis and positive CSF for SARS-CoV2 Impaired consciousness, encephalopathy and encephalitis 11 Decreased level of consciousness And Encephalopathy 22 Articles [ 39 ], [ 40 ], [ 57 ], [ 58 ] [ 60 ], [ 62 ] [ 88 ], [ 96 ], [ 98 ], [ 100 ], [ 101 ], [ 133 ], [ 135 ], [ 136 ] [ 137 ], [ 138 ], [ 139 ] [ 140 ], [ 141 ] [ 178 ] [ 184 ] [ 189 ] [ 195 ] [ 197 ] 4,54 NR in all articles. Yin R et al [ 133 ] reported a 64 Y/O M with altered consciousness and Psychiatric symptoms, his brain CT scan was Normal.…”
Section: Resultsmentioning
confidence: 99%
“… Hosseini AA et al [ 139 ], reported 2 patients (46 Y/O, 79 Y/O) F with Delirium as a presenting feature in COVID-19, neuro-invasion or autoimmune encephalopathy was suggested as the cause. Kulick-Soper CV, et al [ 189 ] reported a 54 Y/O F with bilateral globus pallidus lesions and possibility of hypoxic brain damage. 12 Leukoencephalopathy 3Articles [ 144 ], [ 145 ] [ 188 ] 18 NR in all articles.…”
Section: Resultsmentioning
confidence: 99%
“…Because the SARS-COV-2 pandemic has been a rapidly emergent phenomenon, there is a relatively low number of large-scale retrospective and observational studies reporting neuroradiological findings currently represented in the literature. Consequently, we decided to include 51 case reports and case series in this review for a total of 61 studies ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ) comprising 711 patients. All of these studies used a combination of CT and MRI, with the...…”
Section: Resultsmentioning
confidence: 99%
“…Global hypoxic injury typically manifests on MRI as restricted diffusion of the basal ganglia, thalami, hippocampi, and cortex [61]. Globus pallidus necrosis has been reported in COVID-19, presumably related to hypoxia [62] (Figure 7). Although isolated involvement of the globus pallidus is unusual, it has been described previously in global hypoxic injury [63].…”
Section: Global Hypoxic Injurymentioning
confidence: 99%